AI AS IA: The use and abuse of artificial intelligence (AI) for human enhancement through intellectual augmentation (IA) - Erler, Alexandre; Müller, Vincent C. (The Routledge Handbook of the Ethics of Human Enhancement, 2023)
This paper offers an overview of the technological possibilities and ethics of using AI to achieve human enhancement and more broadly what we call intellectual augmentation (IA). After explaining the central notions of human enhancement, IA, and AI, we discuss the main and most recent technologies for IA, with or without brain-computer interfaces. Given this picture, this paper discusses potential ethical problems, namely inadequate performance, safety, coercion and manipulation, privacy, cognitive liberty, authenticity, and fairness, in more detail. This paper concludes that while there are very significant technical hurdles to real human enhancement through AI, and significant ethical problems, there are also significant benefits that may realistically be achieved in ways that are consonant with a rights-based ethics as well. This paper also highlights the specific concerns that apply particularly to applications of AI for “sheer” IA (more realistic in the near term) and to enhancement applications, respectively.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Engineering & Technology; Health and Social Care; Humanities; Medicine; Dentistry; Nursing & Allied Health; Politics & International Relations; Social Sciences; Sports and Leisure